Evaluation of Tipping, Rotation and rate of space Closure Rate of Canine Retraction by friction less orthodontic techniques (An In vitro Study) - Hussain A Obaidi; Omar Sabah (University of Mosul, College of Dentistry, 2006)
Aim: To evaluate the effect of loops geometry (design) on the rate of space closure, degree of rotation, and degree of tipping. Materials and Methods: The sample consisted of 8 type of loops, namely vertical-loop, vertical with helix-loop, T-loop, readymade loop, PG (universal retraction spring)-loop, opus-loop, teardrop-loop, and L-loop. The method adapted in present study was carried out on Typodont simulation system. The data subjected to the descriptive and variance statistics at 0.05 significant level. Results: There was a significant difference between loops in rate of space closure, rotation and tipping. Vertical loops gave higher significance of rate of space closure and also higher significance degree of rotation and tipping when compared with other loops, while the readymade loop is lowest significance a rate of space closure but it gave low degree rotation and tipping. Although T-loop gave a rate of space closure less than vertical loops but it had the lowest significant degree of rotation and tipping. Conclusion: The T-loop is so more controls and simplest than other loops performing low significance of rotation and tipping tooth movements and achieving higher significance in rate of space closure,